2021
DOI: 10.18632/aging.203776
|View full text |Cite
|
Sign up to set email alerts
|

Maternal adverse childhood experiences before pregnancy are associated with epigenetic aging changes in their children

Abstract: Emerging research suggests associations of physical and psychosocial stressors with epigenetic aging. Although this work has included early-life exposures, data on maternal exposures and epigenetic aging of their children remain sparse. Using longitudinally collected data from the California, Salinas Valley CHAMACOS study, we examined relationships between maternal Adverse Childhood Experiences (ACEs) reported up to 18 years of life, prior to pregnancy, with eight measures (Horvath, Hannum, SkinBloodClock, Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…This is consistent with other studies that reported maternal ACEs prior to pregnancy were associated with longer telomere length and accelerated epigenetic aging in children several years after birth (at ages, 7, 9, and 14), although whether this was linked to gestational age acceleration was not investigated. 54 Mechanistically, early life adversities are likely embedded early in life and contribute to long-term changes in health behaviors (e.g., diet, smoking, physical activity) and psychosocial responses (i.e., stress response, depression, anxiety). 55,56 Eventually, they can have tremendous downstream physiological effects on the affected individual, such as changes in biological functions like the hypothalamic-pituitary-adrenal (HPA) axis and sympathetic nervous system, chronic inflammatory phenotypes, epigenetic alterations, and neural effects, which consequently can lead to pathophysiological states underlying age-related disease susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies that reported maternal ACEs prior to pregnancy were associated with longer telomere length and accelerated epigenetic aging in children several years after birth (at ages, 7, 9, and 14), although whether this was linked to gestational age acceleration was not investigated. 54 Mechanistically, early life adversities are likely embedded early in life and contribute to long-term changes in health behaviors (e.g., diet, smoking, physical activity) and psychosocial responses (i.e., stress response, depression, anxiety). 55,56 Eventually, they can have tremendous downstream physiological effects on the affected individual, such as changes in biological functions like the hypothalamic-pituitary-adrenal (HPA) axis and sympathetic nervous system, chronic inflammatory phenotypes, epigenetic alterations, and neural effects, which consequently can lead to pathophysiological states underlying age-related disease susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the growing awareness of the modulation role of nutrients and other food components on DNAm patterns has paved the way for new studies on the relationship between lifestyle interventions and epigenetic aging ( Mathers et al, 2010 ; Horvath et al, 2014 ; Zannas et al, 2015 ; Quach et al, 2017 ; Franzago et al, 2022 ). Intriguingly, folates, a standard supplementation both in the pre-conception period and during early pregnancy, have been recently investigated in the aging field ( Sae-Lee et al, 2018 ; Monasso et al, 2021 ; Nwanaji-Enwerem et al, 2021a ). Chanachai Sae-Lest et al observed that folic acid plus vitamin B12 intake can provide a different effect depending on MTHFR genotype, proving a decreased epigenetic age in women with the more common 677CC genotype ( Sae-Lee et al, 2018 ).…”
Section: Epigenetic Clocksmentioning
confidence: 99%
“…Since then, aging outcomes have been tied to the epigenetics of early life stress ( Szyf, 2021 ). Moreover, the epigenetics of aging are shown to be altered in the offspring of mothers who themselves experienced childhood trauma ( Nwanaji-Enwerem et al, 2021 ), solidifying a biological basis for transgenerational effects on the aging process. This lifespan approach to understanding maternal care and early life adversity has been validated numerous times and extended to circadian clocks, including the diurnal cortisol rhythm ( Cagampang et al, 2011 ), and systemic diseases, such as cardiovascular disease, diabetes, and metabolic syndrome ( Weaver, 2009 ; Seal and Turner, 2021 ).…”
Section: Nature Via Nurturementioning
confidence: 99%